Use of different carbon sources in cultivation of baker's yeast for production of glycerol-3-phosphate dehydrogenase - Gattas, Edwil A. L. [UNESP] (2013)
The physiological state of yeast cells changes during culture growth as a consequence of environmental changes (nutrient limitations, pH and metabolic products). Cultures that grow exponentially are heterogeneous cell populations made up of cells regulated by different metabolic and/or genetic control systems. The strain of baker's yeast selected by plating commercial compressed yeast was used for the production of glycerol-3-phosphate dehydrogenase. Glycerol-3-phosphate dehydrogenase (GPD) has been widely used in the enzyme assays with diverse compounds of industrial interest, such as glycerol or glycerol phosphate, as well as a number of important bioanalytical applications. Each cell state determines the level of key enzymes (genetic control), fluxes through metabolic pathways (metabolic control), cell morphology and size. The present study was carried out to determine the effects of environmental conditions and carbon source on GPD production from baker's yeast. Glucose, glycerol, galactose and ethanol were used as carbon sources. Glycerol and ethanol assimilations required agitation, which was dependent on the medium volume in the fermentation flask for the greatest accumulation of intracellular GPD. Enzyme synthesis was also affected by the initial pH of the medium and inoculum size. The fermentation time required for a high level of enzyme formation decreased with the inoculum size. The greatest amount of enzyme (0.45 U/ml) was obtained with an initial pH of 4.5 in the medium containing ethanol or glycerol. The final pH was maintained in YP-ethanol, but in the YP-glycerol the final pH increased to 6.9 during growth.